SME financing of Dhaka Bank Ltd.: financing entrepreneurs to enlarge SME industry - Yesmin, Syeda Mahmuda (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.